IMPLEMENTASI NILAI KEADILAN SOSIAL MELALUI DONGENG FABEL BERTEMA KEMISKINAN PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV SEKOLAH DASAR - Mujtahidin; Vita Nurul Fauziyah; Devi Adji Setyorini; Nurjihan Seftinengseh (STKIP Subang, 2026)
Pancasila education in primary schools plays a fundamental role in shaping students’ character, particularly in fostering the value of social justice. However, learning practices that remain overly theoretical often limit students’ understanding of how Pancasila values are applied in real-life situations. This study aims to describe the implementation of social justice values through fable storytelling with a poverty theme in fourth-grade Pancasila Education learning. A qualitative descriptive approach was employed in this research. The learning process was implemented using the Contextual Teaching and Learning (CTL) model and utilized a fable titled “Kancil and the Village Granary Guardian Mouse” as the instructional medium. Data were collected through observation, documentation, and student discussion activities. The findings indicate that fable-based learning enhances students’ understanding of social justice values, increases empathy, and fosters social awareness as well as cooperation among students. Furthermore, the CTL approach encourages active participation, questioning, and the ability to connect learning materials with real-life experiences. Thus, the integration of fable storytelling with contextual learning provides an effective, engaging, and meaningful alternative for Pancasila education in elementary schools.